The effect of virtual instrument system laboratory to enhance technological literacy and problem-solving skills among junior high school students - Supahar Supahar; Eko Widodo (Universitas Negeri Yogyakarta, 2021)
This study aims at analyzing the effect of the Virtual Instrument System Laboratory (Vis-Lab) to enhance technological literacy and problem-solving skills among junior high school students. This type of research can be categorized as Quasi-experimental research with Nonequivalent Control Group Design. The subjects of this study were the seventh-grade students in one of the junior high schools in Sleman Regency, Yogyakarta. The research instrument consisted of pretest and posttest on technological literacy and problem-solving skills. The data analysis technique used N-Gain analysis, prerequisite test, hypothesis testing with MANOVA, and effect size. Based on the MANOVA test, the Sig. value of 0,000 less than α (0.05) indicated that there was a gap in the students’ technological literacy and problem-solving skills between the control and the experimental class. The use of VIS-Lab learning media enhanced the ability of technological literacy by 9.0% for the experimental class and 2.1% for the control class respectively. Meanwhile, the effective contribution to the use of VIS-Lab learning media was 36.5% for the experimental class and 4.73% for the control class. It means that the use of VIS-Lab learning media contribute effectively to improving the ability of technological literacy and problem-solving.